Salivary interleukin-17A and interleukin-18 as potential biomarkers of immunopathogenesis and oral health status in rheumatoid arthritis: Salivary IL-17A and IL-18 in rheumatoid arthritis - Ahmed Abdul-hassan Abbas; Zahraa F. Shaker; Al-Ghurabi, Batool Hassan; Ghaib Nidhal H; Mohammed Ahmed Abdulhassan; Mustafa Ahmed Abdulhassan (Cellular and Molecular Biology, 2025)
Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by persistent inflammation and is often associated with poor oral health. Cytokines play a central role in RA immunopathogenesis. This case-control study investigated the involvement of salivary interleukin-17A (IL-17A) and interleukin-18 (IL-18) in RA patients in relation to oral health status. Unstimulated whole saliva samples were collected from 20 RA patients and 20 age- and sex-matched healthy controls. Oral health was assessed using plaque and gingival indices. Salivary IL-17A and IL-18 concentrations were measured by ELISA. RA patients exhibited significantly higher salivary levels of IL-17A and IL-18 compared to controls (p < 0.05). Both cytokines showed positive correlations with gingival index, and IL-17A was also correlated with disease activity (DAS28). Receiver operating characteristic (ROC) analysis demonstrated that both interleukins effectively discriminated RA patients from healthy controls (AUC = 0.927 for IL-17A, AUC = 0.925 for IL-18). These findings suggest that elevated salivary IL-17A and IL-18 are associated with increased oral inflammation and may serve as non-invasive biomarkers for RA immunopathogenesis and oral health deterioration.